Novel Avenues for Plant Protection: Plant Propagation by Somatic Embryogenesis Enhances Resistance to Insect Feeding - Puentes, Adriana; Högberg, Karl-Anders; Björklund, Niklas; Nordlander, Göran (Frontiers in Plant Science, 2018)
Somatic embryogenesis (SE), a clonal propagation method utilizing somatic cells, occurs under conditions that activate plant stress adaptation mechanisms such as production of protective secondary metabolites. Surprisingly, possible differences in susceptibility to insect pests between SE-generated and conventionally-cultivated plants have not been previously explored. Here, we recorded frequencies and levels of bark-feeding damage by pine weevils (Hylobius abietis) in two large field trials, consisting of emblings (SE-propagated plants) and seedlings from 50 half-sib Norway spruce (Picea abies) families. We found that emblings were less frequently attacked by pine weevils, and when attacked, they were damaged to a lesser extent than seedlings. Moreover, we detected significant additive genetic variation in damage levels received by plants, indicating a heritable component to differences in resistance to insect herbivory among half-sib families. We present first-time evidence that emblings can be more resistant than seedlings to herbivorous insect damage, thus, SE appears to confer a previously-unknown plant protection advantage. This finding indicates novel avenues to explore mechanisms underlying plant resistance and new approaches to develop non-toxic measures against insect pests.